Novel Approach to Control of Robotic Hand Using Flex Sensors - Sandesh R.S; Nithya Venkatesan (Institute of Advanced Engineering and Science, 2014)
This paper discuss about novel design approach to control of a robotic hand using flex sensors which indicates a biomechatronic multi fingered robotic hand. This robotic hand consists of base unit, upper arm, lower arm, palm and five fingers. The aim is to develop an anthropomorphic five fingered robotic hand. The proposed design illustrates the use of 5 micro DC motors with 9 Degrees of Freedom (DOF).Each finger is controlled independently. Further three extra motors were used for the control of wrist elbow and base movement. The study of the DC motor is being carried out using the transfer function model for constant excitation. The micro DC motor performance was analyzed using MATLAB simulation environment. The whole system is implemented using flex sensors. The flex sensors placed on the human hand gloves appear as if they look like real human hand. 89v51 microcontroller was used for all the controlling actions along with RF transmitter/receiver .The performance of the system has been conducted experimentally and studied.